Pneumocystis jirovecii pneumonia in an immunocompetent patient recovered from COVID-19. Issue 5 (4th May 2021) - Viceconte, Giulio; Buonomo, Antonio Riccardo; Lanzardo, Amedeo; Pinchera, Biagio; Zappulo, Emanuela; Scotto, Riccardo; Schiano Moriello, Nicola; Vargas, Maria; Iacovazzo, Carmine; Servillo, Giuseppe; Gentile, Ivan; ,
Abstract: Background: Several cases of invasive fungal diseases in patients with COVID-19 have been reported, mostly due to Aspergillus spp., with anecdotic reports of Pneumocystis jirovecii pneumonia (PJP) as co-infections in immunocompromised patients. We describe the first case of PJP in an immunocompetent patient who recovered from COVID-19 pneumonia. Case description: Our patient was hospitalized for 18 d for respiratory failure due to Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) pneumonia and successfully treated with continuous positive airway pressure (CPAP) respiratory support, enoxaparin, ceftaroline and intravenous 6 mg of dexamethasone for 10 d, then with oral prednisone tapering. Despite his improved radiological and clinical conditions at discharge, he was admitted again after 18 d for worsening of respiratory conditions. Upon the second admission, a high-resolution CT-scan of the chest showed the development of new ground-glass opacities and P. jirovecii was detected on bronchoalveolar lavage fluid. A therapy with trimethoprim-sulphamethoxazole 20 mg/kg and methylprednisolone 40 mg i.v. bis in die (BID) was started, with improvement of clinical, biochemical and radiological conditions. Conclusions: COVID-19 patients may have multiple risk factors for development of PJP, in particular lymphopaenia and use of steroids. PJP must be ruled out with direct microbiological methods in patients presenting with radiologic and clinical features of possible or probable PJP, even in immunocompetent hosts.